Penegakan Hukum terhadap Tindak Pidana Judi Online di Indonesia Analisis Kedudukan Hukum antara Pemain dan Bandar - Putri, Honey; Wardhani , Sri Pramudya (VISA: Journal of Vision and Ideas, 2026)
The development of information technology and the high level of internet penetration in Indonesia have contributed to the increasing prevalence of online gambling, giving rise to legal issues concerning the legal status and criminal law enforcement against online gambling players and operators. This phenomenon is regulated under the Criminal Code and the Electronic Information and Transactions Law, which normatively distinguish the role of players as passive offenders and operators as active offenders in the organization of online gambling. This study aims to analyze the differences in legal standing between players and online gambling operators, as well as to examine the implementation of criminal law enforcement against both parties in practice. The research employs a normative legal research method with a qualitative descriptive-analytical approach, conducted through literature review and analysis of law enforcement practices, including a case study of online gambling enforcement in the Special Region of Yogyakarta. The findings indicate that, normatively, operators are subject to heavier criminal sanctions due to their active and systematic roles, while players are positioned as offenders with a lighter degree of criminal liability. However, in practice, criminal law enforcement tends to focus more on players due to the ease of proof, jurisdictional limitations, and technical obstacles in reaching online gambling operators. The study concludes that there is a gap between normative legal regulation and the implementation of criminal law enforcement against online gambling offenses in Indonesia.